Airway autoimmunity, asthma exacerbations, and response to biologics. Issue 12 (3rd September 2022) - Venegas Garrido, Carmen; Mukherjee, Manali; Bhalla, Anurag; Nair, Parameswaran
Abstract: Biologic therapies in asthma are indicated in severe disease, and they are directed against specific inflammatory modulators that contribute to pathogenesis and severity. Currently approved biologics target T2 cytokines (IgE, IL‐5, IL‐4/IL‐13, and TLSP) and have demonstrated efficacy in clinical outcomes such as exacerbation rate and oral corticosteroid dose reductions, blood and airway eosinophil depletion, and lung function improvement. However, a proportion of these patients may show inadequate responses to biologics, with either initial lack of improvement or clinical and functional worsening after an optimal initial response. Exacerbations while on a biologic may be due to several reasons, including imprecise identification of the dominant effector pathway contributing to severity, additional inflammatory pathways that are not targeted by the biologic, inaccuracies of the biomarker used to guide therapy, inadequate dosing schedules, intercurrent airway infections, anti‐drug neutralizing antibodies, and a novel phenomenon of autoimmune responses in the airways interfering with the effectiveness of the monoclonal antibodies. This review, illustrated using case scenarios, describes the underpinnings of airway autoimmune responses in driving exacerbations while patients are being treated with biologics, device a strategy to evaluate such exacerbations, an algorithm to switch between biologics, and perhaps to consider two biologics concurrently.